2021
DOI: 10.1038/s41598-021-83385-9
|View full text |Cite
|
Sign up to set email alerts
|

Bioabsorbable nerve conduits three-dimensionally coated with human induced pluripotent stem cell-derived neural stem/progenitor cells promote peripheral nerve regeneration in rats

Abstract: Peripheral nerve regeneration using nerve conduits has been less effective than autogenous nerve grafts. To overcome this hurdle, we developed a tissue-engineered nerve conduit coated with mouse induced pluripotent stem cell (iPSC)-derived neurospheres, for the first time, which accelerated nerve regeneration in mice. We previously demonstrated the long-term efficacy and safety outcomes of this hybrid nerve conduit for mouse peripheral nerve regeneration. In this study, we investigated the therapeutic potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 58 publications
(33 reference statements)
0
24
0
1
Order By: Relevance
“…To further verify the function of 3D SLCs, a widely used sciatic nerve injury model was used to explore their effect on PNI repair in vivo 29 , 34 . The results showed that ADSC, conventional SLC, and 3D SLC transplantation could improve the SFI and prevent denervation-induced gastrocnemius muscle atrophy.…”
Section: Discussionmentioning
confidence: 99%
“…To further verify the function of 3D SLCs, a widely used sciatic nerve injury model was used to explore their effect on PNI repair in vivo 29 , 34 . The results showed that ADSC, conventional SLC, and 3D SLC transplantation could improve the SFI and prevent denervation-induced gastrocnemius muscle atrophy.…”
Section: Discussionmentioning
confidence: 99%
“…The results from the autograft were slightly better than the therapeutic option. However, the group with the cells showed higher axon number and good outcomes making this other promising cell-based therapy using NGCs in the PNI treatment [78].…”
Section: 41mentioning
confidence: 95%
“…f ) Reproduced with permission. [93] Copyright 2021, Springer Nature. [99] , and b) Representative stressstrain curves of the shell, core, and tendon scaffold in a) and the H&E staining images of the regenerated tissues near shell and in core.…”
Section: Polymeric Scaffolds For Soft Connective Tissues Regenerationmentioning
confidence: 99%
“…d) Cross-sectional H&E staining images of regenerated nerves obtained [8]. e) Fabricated NGC (left top), the cross-sectional SEM image (right top), the neurospheres derived from the hiPSCs (left bottom), and the seeding of hiPSC-derived neurospheres on the NGC in vitro (right bottom) [93]. f ) Bar graphs of regenerated axon numbers and axon area from the control group (NGC alone), iPSC-scaffold, and autograft [93].…”
mentioning
confidence: 99%